2016
DOI: 10.1039/c5ra17867c
|View full text |Cite
|
Sign up to set email alerts
|

Direct transition mechanism for molecular diffusion in gas hydrates

Abstract: In this work, we use dual cage explicit atomic systems to demonstrate theoretically that direct transitions are feasible through hexagonal and pentagonal faces in type I hydrate without compromising the overall structure integrity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 31 publications
(27 reference statements)
1
20
0
Order By: Relevance
“…The methane diffusion probed in the present study is much faster than that reported in the literature for the cage-to-cage hopping of CH 4 molecules through clathrate sI. Cage-to-cage hopping is a rare event that requires distortion of the host network 36 and the associated diffusion coefficient is of the order of 10 −11 to 10 −12 cm 2 s −1 at 250 K, as revealed by experimental 21 and computational 24 studies. Similar conclusions have been reported for the cage-to-cage hopping of other guest molecules 37 , 38 , including molecules forming clathrate sII 37 .…”
Section: Discussionsupporting
confidence: 42%
“…The methane diffusion probed in the present study is much faster than that reported in the literature for the cage-to-cage hopping of CH 4 molecules through clathrate sI. Cage-to-cage hopping is a rare event that requires distortion of the host network 36 and the associated diffusion coefficient is of the order of 10 −11 to 10 −12 cm 2 s −1 at 250 K, as revealed by experimental 21 and computational 24 studies. Similar conclusions have been reported for the cage-to-cage hopping of other guest molecules 37 , 38 , including molecules forming clathrate sII 37 .…”
Section: Discussionsupporting
confidence: 42%
“…This way, it is possible to retain approximately the shape and volume of the crystal cells and to allow some degree of flexibility in the structure. This type of approximation was successfully applied to a system of two cages in the sI clathrate hydrate for studying the intercage transition of CH 4 and CO 2 in a previous work . Then, one of the central cages of 1L and 2L systems was filled with a single H 2 molecule, with the aim to determine the optimal position of the guest.…”
Section: Resultsmentioning
confidence: 99%
“…This type of approximation was successfully applied to a system of two cages in the sI clathrate hydrate for studying the intercage transition of CH 4 and CO 2 in a previous work. 60 Then, one of the central cages of 1L and 2L systems was filled with a single H 2 molecule, with the aim to determine the optimal position of the guest. The resulting optimal geometry of just one occupied cage is illustrated in Figure 3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transport of guest molecules through the lattice, and their potential for reaction are clearly relevant to applications that involve storage (particularly of hydrogen) and this has motivated several computational investigations. [13][14][15] On the experimental side, the standard tools used for clathrate characterization (X-ray and neutron diffraction, solid-state NMR, and Raman spectroscopy) 16 are not generally suitable for studying guest transport and reactions (although not impossible). 17 A more direct approach is to create isolated reactive species and monitor their behaviour with a specific probe (e.g.…”
Section: Introductionmentioning
confidence: 99%